Efektivitas Program KALIMASADA Dalam Meningkatkan Kesadaran Masyarakat Akan Pentingnya Administrasi Kependudukan di Kelurahan Kendangsari - Lukman Arif; Shofwatun Nailul Isti'anah (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
The effectiveness of the KALIMASADA (Population Administration Aware Community Environmental Area) program in raising public awareness about the importance of managing population administration is discussed in this study. The aim of the KALIMASADA program is to make it easier for the community to process population administration documents by making it possible to handle the KALIMASADA pilot RT head or at the nearest RW hall instead of having to go directly to the Surabaya City Population and Civil Registry office. This study uses a qualitative approach with an emphasis on descriptive techniques. Target accuracy, program socialization, program objectives, and also program monitoring are four aspects that affect whether or not a program runs using Budiana's variable theory of effectiveness (2007). The results of research on the implementation of the KALIMASADA program in the Kendangsari Village can be said to have been effective. However, it needs to be improved again in several aspects such as program socialization so that citizen awareness of the importance of population administration can be further increased so that an orderly population administration area is realized.